Solusi Terhadap Penderita Disleksia dan Disgrafia - Susanti, Ari; Ngatmini, Ngatmini (Multiverse: Open Multidisciplinary Journal, 2024)
This study focuses on improving the reading and writing abilities of students with dyslexia and dysgraphia through specific strategies. The research question centers on how these strategies can aid students struggling with reading and writing. The methods employed are qualitative and a literature review from relevant journal sources. The research was conducted at SDN Karakan 01, Weru District, Sukoharjo Regency, with a fifth-grade student named Fatin Aisyah Rani as the subject. The results indicate that through strategies, collaboration with parents, individual assistance, homework assignments, motivation, engaging learning media, and appropriate teaching methods, Fatin was able to write 3 to 4 words, read two to four syllables, and began to feel more confident, as evidenced by increased interaction with peers. The conclusion is that appropriate strategies can effectively enhance the reading and writing skills of students with dyslexia and dysgraphia.